CFD study of heat and mass transfer and entropy generation in a 3D solar distiller heated by an internal column. (March 2019) - Al-Rashed, Abdullah A.A.A.; Oztop, Hakan F.; Kolsi, Lioua; Boudjemline, Attia; Almeshaal, Mohammed A.; Ali, Mohamed E.; Chamkha, Ali
Highlights: The heat and mass transfer inside a 3D solar distiller is studied. The 3D vector-potential-vorticity formalism is used to develop the governing equation. Complex flow structure and temperature and concentration fields occurs. Entropy generation is evaluated. Abstract: Three-dimensional computational analysis was performed to investigate the double diffusive natural convection inside a cubical solar distiller heated by a square-shaped column. Governing equations were developed using the 3D vector potential-vorticity and solved using the finite volume method. Different governing parameters, i.e., Rayleigh number 10 3 ≤ Ra ≤ 10 5, buoyancies ratio −10 ≤ N ≤ 10, geometrical parameter 0.1 ≤ L h ≤ 0.7 for Le = 0.85 and Pr = 0.7 corresponding to humid air, were tested. It was found that both heat and mass transfer are strongly affected by the change of buoyancy ratio, geometrical parameter and Rayleigh number. Graphical abstract: Image, graphical abstract